Utility of myocardial work by echocardiography in the early diagnosis of cardiotoxicity - Denise Cortes-Pérez; Diana Romero-Zertuche; Gabriela Rodríguez-Guzmán; Itzel Calixto-Guízar; Carlos Martínez-Hernández (Exploration of Cardiology, 2025)
Aim: Evaluate the role of myocardial work by echocardiography and determine its utility as an early diagnosis of cardiotoxicity. Methods: Single-center included 180 patients over 18 years old undergoing chemotherapy, the definition of cardiotoxicity for this study was to observe a left ventricular ejection fraction (LVEF) less than 50% and, or a global longitudinal strain (GLS) less than 16%. With these parameters, we divided the population into two groups, with cardiotoxicity and without cardiotoxicity. ROC curves were performed to determine the best cut-off point for global myocardial work to define cardiotoxicity. 2 × 2 tables were made to calculate sensitivity, specificity, positive predictive value, and negative predictive value. Results: Cardiotoxicity was established by obtaining cutoff points for global myocardial work index (GWI) with values lower than 1,381.5 mmHg%, Global Constructive Work (GCW) of 1,722 mmHg%, and myocardial efficiency [Global Work Efficiency (GWE)] of 88.5%, with a sensitivity (58.8%, 65.6%, and 52.9%) and specificity (91.8%, 82.1%, and 89.6%) respectively. Conclusions: We propose the measurement of myocardial work as a diagnostic tool for cardiotoxicity, as it has good specificity and negative predictive value, serving as an early diagnostic tool for cardiotoxicity without waiting for a decrease in LVEF and without being a marker influenced by loading conditions, in patients undergoing antineoplastic treatment.